Membimbing Umat Melalui Program Ngaji Bisnis di Lembaga Sosial Teras Dakwah - Ahmad Syamsul Muarif; Iin Handayani (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
The purpose of this article is to examine the "study business" program as a new idea in boosting the interest of young people who want to become more religious, wealthier, successful, on the pilgrimage, and enter heaven. This article uses descriptive qualitative research, data collection methods through observation and interviews, with analysis techniques using data reduction, data presentation and drawing conclusions. The results showed that the process of implementing the "study business" program in the Da’wa Terace was by telling stories about the actions of business by Gus Madkhan and Haji Thariq, giving material from bankruptcy, having a lot of debt, giving alms to rising and building businesses to become successful. With this program, young people are interested in trying to open a business or open business opportunities in order to achieve success, become rich so that they can give alms more, can go on pilgrimage, become pious people and then go to heaven.